The Influence Of Work Competence And Work Stress On Performance With Job Satisfaction As A Mediation Variable - Mohammad Hakim Mustaqim; Mafizatun Nurhayati; Setyo Riyanto (International Journal of Management and Business Applied, 2023)
The purpose of this study was to determine the impact of competence and work stress on teacher performance in elementary schools, with job satisfaction as a mediating variable. This study used a causal quantitative method with a population of 161 teachers at the Cipinang Besar Selatan V elementary school and covered the entire population. The results of the study show that teacher competence has a positive and significant impact on performance. Work stress has a negative and significant impact on teacher performance. This study also found that teacher competency has a positive and significant impact on job satisfaction. The dimension of personality competence in teacher commitment has the greatest influence on job satisfaction. Job stress has a negative and significant impact on job satisfaction, with the response factor to ambiguity in work stress having the greatest influence. In addition, this study also shows that job satisfaction has a positive and significant impact on performance. Co-worker dimensions of job satisfaction have the greatest influence on teacher performance. This study also found that job satisfaction can function as a mediating variable between competence and teacher performance, with the complementary effect as the mediating effect. Likewise, job satisfaction can also be a mediating variable between work stress and teacher performance, with a mediating effect that also occurs, namely the Complimentary Effect.